An Inquiry-Based Teaching Model for Nursing Professional Courses Based on Data Mining and Few-Shot Learning Technology - Fuling Fan (Computational Intelligence and Neuroscience, 2022)
Teaching is defined as a relatively stable structural framework and activity process of teaching activities established under the guidance of specific teaching concepts and theories. It serves as a link between teaching theory and practice, as well as between the teaching system’s static and dynamic conditions. The ITM (Inquiry-Based Teaching Model) has received a lot of attention and has been used in a lot of classrooms. Data mining (DM) is a method for discovering knowledge in databases and a technology for mining information in large data sets. It is primarily used to discover unknown relationships and patterns in related data. This paper applies DM’s core technology, particularly the decision tree algorithm, to give hospital managers more comprehensive and in-depth data analysis capabilities, as well as strong technical support for hospitals in developing management plans. Furthermore, due to the scarcity of research data in the nursing profession, this paper introduces the few-shot learning technology to improve the model’s analysis ability.